Technical Scrutiny of Block chain Technology Protocols and its Applications - S, Madhura; Luharuka, Shubham; Kulkarni, Gaurav Anil; Sri, Pallothu Devi; Somani, Ria (IRO Journal on Sustainable Wireless Systems, 2020)
Block chain technology is one which is evolving over time and is still brand new to the mindset of various people. The question of how to use it even if one has the want to use it arises thereby questioning its need in necessary functioning. This technology may be hand in hand if required for the following features:-Various distributed participants; lack of trust in mediating parties; if maximum work is done through transactions. A need to reduce manual labor and be comfortable with digital listing of activities to avoid disputes. When one has a real time need of sharing the various activities with other clients/partners and get a valid and crisp work history. In this paper the importance of block chain and its implications are presented along with various case studies of technical glitches whether in IoT or banking sectors, this paper covers it all.
Keywords: Block Chain; IoT; machine learning; Artificial Intelligence